2016
DOI: 10.19071/jpsp.2016.v2.3025
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Zinc Interaction Influence Leaf Area Index in Fine vs. Coarse Rice (Oryza sativa L) Genotypes in Northwest Pakistan

Abstract: Leaf area index (LAI) is a measure of leafiness per unit ground area and denotes the extent of photosynthetic machinery is an important growth and yield-determining factor because it is a major determinant of light interception and transpiration. Phosphorus (P) and zinc (Zn) are the most important factors affecting LAI of rice (Oryza sativa L.). A field experiment was conducted to assess the impact of phosphorus (0, 40, 80, 120 kg P/ ha) and zinc levels (0, 5, 10, 15 kg Zn/ha) on LAI of rice (O. sativa L.) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
0
0
Order By: Relevance
“…In general, leaf area growth is mainly influenced by nutrients and modified by N addition [20] however determination of leaf size is complicated and runs counter to prediction [21]. The results of the present study confirm that N and K combined at high levels was more beneficial in terms of leaf size, probably due to their implication in plant growth, as shown for other nutrient combination [22].…”
Section: Sift Desk Discussionsupporting
confidence: 75%
“…In general, leaf area growth is mainly influenced by nutrients and modified by N addition [20] however determination of leaf size is complicated and runs counter to prediction [21]. The results of the present study confirm that N and K combined at high levels was more beneficial in terms of leaf size, probably due to their implication in plant growth, as shown for other nutrient combination [22].…”
Section: Sift Desk Discussionsupporting
confidence: 75%
“…Increasing P fertilization at P1, P2 and P3 increased the LAI of oil palm seedlings to optimum levels. Amanullah et al [16] reported that P and zinc (Zn) were the most important factors influencing rice LAI. P deficiency affects the relative rates of leaf area expansion and plant growth during the early stages.…”
Section: Leaf Area Index and Light Use Efficiencymentioning
confidence: 99%